Development of wireless communications using software defined radio - Tan, Pei Yu. (2009)
In this project, Development Wireless Communications Using Software Defined Radio, the focus will be at creating a GSM Base Station using Software Radio. The objective is to make use of the Universal Software Radio Peripheral (USRP) to mimic the GSM network and create a Base Station that handles call request from mobile phones as well as paging mobile phones; all these being build using software radio.